Assessment of the Degree of Left Atrial Fibrosis in Patients with Different Forms of Atrial Fibrillation - Eugene O. Perepeka; Elina V. Bodnarevska; Mykhailo S. Ishchenko; Borys B. Kravchuk (Український журнал серцево-судинної хірургії)
Atrial fibrillation (AF) is the most common type of cardiac arrhythmia, which has a significant impact on the health of patients worldwide. Left atrial fibrosis (LAF) is considered an irreversible form of remodeling that occurs in response to inflammation, stretching, or overload of the left atrium. The prevalence and degree of LAF may be associated with the prognosis and treatment outcomes after catheter ablation.